Izboljšanje dihalne funkcije s kratkim bolnišničnim programom respiratorne terapije pri osebi s kronično tetraplegijo - prenos metode glosofaringealnega dihanja v klinično prakso v Sloveniji - Puzić, Nataša (Rehabilitacija (Ljubljana), 2014)
Introduction: In persons with chronic cervical spinal cord injury, respiratory functions are impaired due to respiratory muscles paralysis and often worsen in time because of complications and ageing. A 30-year-old male with chronic tetraplegia (15 years, level C3, AIS A) and with a tracheotomy tube had preserved diaphragmal activity, but low respiratory volumes, needed several aspirations per day and had frequent respiratory tract infections. A certified apnea instructor previously transferred the glossopharyngeal breathing method to six physiotherapists at the University Rehabilitation Institute in Ljubljana. The aim of a comprehensive respiratory muscles training and therapy program was to improve respiratory functions and decrease complication rates. Methods: A three-week in-patient respiratory program consisted of inspiration and expiration muscle training, learning and performing of the glossopharyngeal breathing and of regular use of mechanical insufflation%exsufflation. The patient continued the training at home, at least three times a week. Results: At the end of the program and at the 4 month follow-up there was an improvement in vital capacity, maximum inspiratory and expiratory pressures. The speech improved. The number of aspirations per day decreased and no respiratory tract infection occurred. Conclusion: In a patient with chronic C3 tetraplegia a short comprehensive inpatient respiratory therapy program followed by training at home can improve respiratory functions and decrease complication rates. From the world of extreme sports, the glossopharyngeal breathing method was transferred to clinical practice in Slovenia at the University Rehabilitation Institute in Ljubljana.
Keywords: chronic tetraplegia; glosofaringealno dihanje; glossopharyngeal breathing; kronična tetraplegija; respiratorna terapija; Respiratory Therapy